Análise econômico-financeira de aviários para a integração de frangos de corte sob condições de risco - Simões, Danilo [UNESP]; Ribeiro, João Paulo; Gouveia, Pedro Rodrigo; dos Santos, Josiane Corrêa (FapUNIFESP (SciELO), 2015)
Financial investment projects are characterized by uncertainties. When quantified, these will determine the probability of their occurrence and the condition of risk. This information might be analyzed via simulation of Monte Carlo Method, which will establish the level of associated risk. To understand the financial risks of broiler production in integration system, cash flow models for aviaries were formulated with different technological levels. Using deterministic techniques, the value of the main economic viability indicators were calculated, which were incorporated to the risk through a probabilistic model of pseudo-random numbers, generated with Monte Carlo Method. The uncertainties associated to financial projects show that broiler production in different integration systems is economically viable. However, the best financial return and smallest risk are obtained with an aviary which contains low technological level and the least financial investment.
Economical and financial analysis of aviaries for the integration of broilers under conditions of risk
Keywords: Agribusiness; Monte carlo method; Net present value; Production cost; Simulation